The Parisian Jesuits and the Enlightenment 1700-1762 - Northeast, C (Voltaire Foundation, 2017)
One of the most fruitful developments in Enlightenment historiography in recent years has been an increased awareness of the social conditions of intellectual activity. Studies of ‘reading, writing and publishing’ in eighteenth-century France have emphasised the shared ground between Catholics and non-Catholics by casting the philosophes in a conservative light as would-be infiltrators of existing cultural institutions. Members of the ‘patrician’ Enlightenment like Voltaire, Montesquieu or Diderot shared with Catholic writers common publishing constraints, common personal aspirations and, above all, common notions of the cultivated audience they wished to address. The first chapter seeks to situate the Jesuit hommes de lettres within their social environment, the literary and journalistic milieux of Paris, to consider the assumptions which governed their literary relations and to examine the limits of mutual toleration between the Society of Jesus and anti-Christian writers. This forms the essential background for the more conventional history of ideas which follows. The three central chapters, on philosophy, criticism, and the treatment of pagan religions, focus on the actual nature of Enlightenment irreligion. The aim is neither to provide a comprehensive survey of Jesuit thought in these areas nor simply to catalogue the Society’s ‘response’ to the philosophes, but rather to isolate key problems which arose for the Jesuits in their account of Christianity. Judging from the Jesuit experience, should eighteenth-century Catholic thought best be conceived as a fixed orthodoxy or as the result of a complex process of intellectual change and readjustment involving both Christians and unbelievers? Preface 1. The Jesuits and Parisian literary life The Jesuit writers and their activities, 1700 to 1735 The Jesuits in literary and scholarly society, to 1735 The premisses of a Christian literature The problem of Jansenist literature Relations with irreligious writers, to 1735 Later literary relations, 1735 to 1762 2. Christianity: the philosophical problems Faith and reason: the premisses of Jesuit philosophy Natural knowledge: the scope of philosophical proofs Atheism: the debate over universal consent Atheism: the analysis of contemporary philosophers Divine providence The soul Faith and reason in later Jesuit apologetics 3. Christianity: the critical problems The limits of textual criticism: i. The Bible The limits of textual criticism: ii. The Fathers The Bible and history Miracles and prophecies Pagan sources and Christian apologetics Criticism and faith: the sceptical solution 4. Natural and revealed religion Non-Christian religions: the theological premisses The Jesuits and deism The ‘natural history’ of religion 5. The Jesuits in Enlightenment thought ‘Molinism’ and secular literature Reflections on the Society’s social and political role The verdict of the Jesuit renegades Conclusion Bibliography Index